Waktu respon untuk operasi caesar darurat dan dampaknya terhadap hasil maternal dan neonatal: A scoping review - Dewi, Bella Rossana; Sriatmi, Ayun; Widjanarko, Bagoes (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The decision-to-delivery interval (DDI) is a critical factor in emergency caesarean section, with the National Institute of Clinical Excellence (NICE) recommending a maximum of 30 minutes. However, adherence to this standard varies globally, particularly in resource-limited countries, contributing to an increased risk of maternal and neonatal complications. Purpose: To analyse response time to emergency caesarean section and its impact on maternal and neonatal outcomes. Method: A scoping review of PubMed, Scopus and Google Scholar databases was conducted to analyse studies published between 2014-2024 that addressed DDI, maternal complications and neonatal outcomes. Results: Many developing countries struggle to meet the DDI standard of ≤30 minutes due to limited infrastructure, medical team readiness and operational processes. Studies have shown that this delay increases the risk of perinatal death, maternal complications and the need for neonatal intensive care. Although not always directly impacting neonatal outcomes, factors such as medical staff readiness and system efficiency play a role. Therefore, improving the health system and optimizing medical team coordination are needed to improve emergency caesarean section services. Conclusion: Delayed Decision-to-Delivery Interval in emergency caesarean sections, especially in developing countries, is caused by operational inefficiency, limited infrastructure, and suboptimal medical team coordination. This has an impact on increasing maternal and perinatal mortality rates and the need for intensive care. Systemic improvements and mitigation strategies, such as intrauterine resuscitation, are needed to improve the quality of emergency obstetric care globally. Keywords: Emergency Caesarean Section; Maternal; Neonatal. Pendahuluan: Interval keputusan-ke-persalinan/decision-to-delivery interval (DDI) merupakan faktor krusial dalam operasi caesar darurat, dengan National Institute of Clinical Excellence (NICE) merekomendasikan batas maksimal 30 menit. Namun, kepatuhan terhadap standar ini bervariasi secara global, terutama di negara dengan sumber daya terbatas yang berkontribusi pada peningkatan risiko komplikasi maternal dan neonatal. Tujuan: Untuk menganalisis waktu respon untuk operasi caesar darurat dan dampaknya terhadap hasil maternal dan neonatal. Metode: Penelitian scoping review dari basis data PubMed, Scopus, dan Google Scholar untuk menganalisis studi yang dipublikasikan antara tahun 2014-2024 yang membahas DDI, komplikasi maternal, dan luaran neonatal. Hasil: Banyak negara berkembang mengalami kesulitan memenuhi standar DDI ≤30 menit akibat keterbatasan infrastruktur, kesiapan tim medis, serta proses operasional. Studi menunjukkan bahwa keterlambatan ini meningkatkan risiko kematian perinatal, komplikasi maternal, dan kebutuhan perawatan intensif neonatal. Meskipun tidak selalu berdampak langsung pada hasil neonatal, faktor seperti kesiapan tenaga medis dan efisiensi sistem turut berperan. Oleh karena itu, perbaikan sistem kesehatan dan optimalisasi koordinasi tim medis diperlukan untuk meningkatkan layanan operasi caesar darurat. Simpulan: Keterlambatan Interval Keputusan-ke-Persalinan dalam operasi caesar darurat, terutama di negara berkembang disebabkan oleh ketidakefisienan operasional, keterbatasan infrastruktur, dan koordinasi tim medis yang kurang optimal. Hal ini berdampak pada peningkatan angka kematian maternal dan perinatal serta kebutuhan perawatan intensif. Perbaikan sistemik dan strategi mitigasi, seperti resusitasi intrauterin diperlukan untuk meningkatkan kualitas perawatan obstetri darurat secara global. Kata Kunci: Maternal; Neonatal; Operasi Caesar Darurat.